FEASIBILITY STUDY ON SUPERSONIC CENTRIFUGE FOR FREE WATER REMOVAL FROM BIOGAS - AHMAD ZAINUDIN, MUHAMMAD FAIZ (Universiti Teknologi PETRONAS, 2017)
Biogas is one of a well-known renewable energy sources which is not only useful as alternative fuels but also gives positive environmental benefits. A total amount of 70 m³ biogas released for each ton of crude palm oil (CPO) production from palm oil mill effluent (POME) will only be a waste of potential energy and revenue source as well as endangering the environment due to significant global warming effect of releasing methane if not being managed efficiently. Rapid development and biogas utilization is taking place all over the world, especially for the largest producer of palm oil, Malaysia. Consequently, the utilization of biogas is facing significant challenges in terms of purification and upgrading to meet the quality requirement for various end usage. In order to utilize biogas in energy efficient systems and for power generation, it has to be purified and have highest methane content and lowest impurities content as possible.